1976
DOI: 10.1007/bf01886120
|View full text |Cite
|
Sign up to set email alerts
|

Review: Artifical ventilation with positive end-expiratory pressure (PEEP)

Abstract: CPPV (continuous positive pressure ventilation) is obviously superior to IPPV (intermittent positive pressure ventilation) for the treatment of patients with acute respiratory insufficiency (ARI) and results within a few minutes in a considerable increase in the oxygen transport. The principle is to add a positive end-expiratory plateau (PEEP) to IPPV, with a subsequent increase in FRC (functional residual capacity) resulting in re-opening in first and foremost the declive alveolae, which can then once again t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The risks were explained in studies from several years ago. 2,3 The conclusion in this trial was that managing V D /V T may be clinically useful, but that particular parameter was one of the least statistically significant in their Table 2.…”
Section: Dead Space Fraction: One Of Many Choices To Assess Peep Titrmentioning
confidence: 83%
See 1 more Smart Citation
“…The risks were explained in studies from several years ago. 2,3 The conclusion in this trial was that managing V D /V T may be clinically useful, but that particular parameter was one of the least statistically significant in their Table 2.…”
Section: Dead Space Fraction: One Of Many Choices To Assess Peep Titrmentioning
confidence: 83%
“…Therefore, treating the anemia or low cardiac output should be done first, and mild hypoxemia may be acceptable in some situations, as reported by Martin et al 3 They suggested that hypoxia triggers a complex network of cellular signaling pathways that may result in protective responses. 3 Protocol-driven F IO 2 titration should be combined with a clear understanding that high F IO 2 We thank Dr Alkhuja and Ms Duffy for reviewing our paper, their thoughtful insight about the physiology of oxygen delivery, and their call for education of health care staff about the same. We agree with their ideas about optimization of cardiac output and anemia for increasing oxygen delivery when required to do so.…”
Section: Practice Of Excessive F Io 2 and Effect On Pulmonary Outcomementioning
confidence: 99%
“…Lung inflation activates vagal pulmonary afferents (1) that promote dopamine release in the brain stem (13). An increase in lung volume also results in vagally mediated inhibition of expiratory muscle activity, which can increase FRC (39) and VPR (45). Thus when metabolic demand and CO 2 production increase inspiratory effort, suppression of expiratory motor output might improve chest wall compliance with favorable consequences on FRC and VPR.…”
Section: Discussionmentioning
confidence: 97%
“…The differences between the protein-free and the protein-containing LSF preparations were even more pronounced if dose-response comparisons were performed based on the Pao2 values during the 2nd PEEP reduction. It is well known that PEEP by itself has beneficial effects on oxygenation (Stokke, 1976). Thus, if a moderately active LSF like Exosurf or PL-LSF is combined with ventilation under high PEEP, it is possible to re-establish gas exchange in the lung (Rider et al, 1992).…”
Section: Discussionmentioning
confidence: 99%